The contribution of icons to the information value of symbols and other representations - Winfried Nöth (Informatio)
Peirce distinguishes between information which symbols imply and information which symbols convey. All symbols imply information, but only propositional symbols (dicents) can convey information. The information a symbol implies is the store of knowledge accumulated in it minus the signification contained in its definition. The information a symbol conveys is the new knowledge an interpreter derives from it in the form of a propositions of which it is the subject or predicate. Only symbols, not icons or indices, imply information. According to Peirce’s early theory (1865–68), information is the product of the quantities of signification and denotation of a symbol. Peirce’s later semiotic theory reinterprets information as a result of the interplay between icons, indices, and symbols. Denotation is reconsidered in terms of indexicality, signification in terms of iconicity. Neither symbols nor icons or indices can convey information alone. Sentence subjects are reinterpreted as conveying indexical, and predicates as iconic information. The icons through which symbols convey information are mental images, which are interpretants of the symbol. The paper examines why Peirce attributes to icons a «dream exciting power» and why the qualities signified by them are somehow «of the nature of a sleeping consciousness».